Sustainable machining - correlation of the optimization by minimum energy, minimum manufacturing time and cost of production - Pascoal, Filipa; Silveira, José (Cranfield University Press, 2013)
The machining process leads the indices of productivity and employability in a world level and has an enormous influence at social and economics standards, however it requires machinery that consume high levels of energy, chemical fluids and has great emissions of greenhouse gases. In our days as governments and clients increase their demands for the degradation of ecosystems, also increase the need for companies to implement sustainable policies and improve their environmental performances. The reduction of energy consumption and consequently the reduction of fossil supplies are a major source of concern at this level. This article establish a bridge between the classical approaches of optimization models of machining processes (Maximizing Production Rate and Minimizing Production Cost), and reduction of electricity. For a single pass turning it was used a mathematical model to analyse the data taken as a reference, optimizing the critical parameters of consumption of time, money and energy.
Keywords: Machining; Sustainability; Optimization